2018
DOI: 10.1111/papt.12180
|View full text |Cite
|
Sign up to set email alerts
|

Relations of mindfulness facets with psychological symptoms among individuals with a diagnosis of obsessive–compulsive disorder, major depressive disorder, or borderline personality disorder

Abstract: The study showed deficits in mindfulness scores in all diagnostic groups compared to a healthy control group. Overall, mindfulness construct has a significantly negative association with indexes of global distress, dissociative symptoms, alexithymia, and depression. Mindfulness-based interventions in clinical settings should take into account different patterns of mindfulness skills and their impact on disease-specific maladaptive cognitive strategies or symptomatology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
22
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 73 publications
(101 reference statements)
5
22
1
Order By: Relevance
“…The first hypothesis was supported as treatment-seeking adults with clinically significant OCD symptoms reported significantly lower trait mindfulness and self-compassion than healthy controls (in line with findings from Crowe and McKay (2016), Didonna et al (2018) and Emerson et al (2017)) and treatment-seeking adults with clinically significant depression and/or anxiety symptoms. This provides initial support for the notion that adults with OCD may experience particular challenges with being mindful and selfcompassionate, even relative to people with other common mental health problems.…”
Section: Summary Of Resultssupporting
confidence: 61%
See 3 more Smart Citations
“…The first hypothesis was supported as treatment-seeking adults with clinically significant OCD symptoms reported significantly lower trait mindfulness and self-compassion than healthy controls (in line with findings from Crowe and McKay (2016), Didonna et al (2018) and Emerson et al (2017)) and treatment-seeking adults with clinically significant depression and/or anxiety symptoms. This provides initial support for the notion that adults with OCD may experience particular challenges with being mindful and selfcompassionate, even relative to people with other common mental health problems.…”
Section: Summary Of Resultssupporting
confidence: 61%
“…obsessive beliefs, are accounted for. Five further studies with clinical (Didonna et al 2018;Hawley et al 2017) and nonclinical samples (Crowe and McKay 2016;Emerson et al 2017;Solem et al 2015) found that OCD symptoms were negatively associated with (facets of) mindfulness and that adults with clinically significant OCD symptoms demonstrated lower trait mindfulness (facets) relative to healthy controls.…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…Another promising avenue of investigation is mindfulness, which can be viewed as a set of skills that incude: labelling internal experiences with words, noticing or attending to external or internal experiences (e.g., sensations, emotions, cognitions), attending to one’s activities of the moment, taking a nonevaluative stance toward thoughts and feelings, and allowing thoughts and feelings to come and go, without becoming absorbed in their content and without getting carried away by them [25]. Different diagnostic groups showed deficits in mindfulness skills [26] and previous research has underscored the need for addressing the role of emotion regulation in the link between mindfulness and well-being [27]. Furthermore, describing internal experiences with words and acting with awareness were important for PWB, especially for individuals with internalizing traits (e.g., augmented stress reactivity and negative affect directed inward) [28].…”
Section: Introductionmentioning
confidence: 99%